2011
DOI: 10.1093/infdis/jir639
|View full text |Cite
|
Sign up to set email alerts
|

Human Cellular Immune Response Against Giardia lamblia 5 Years After Acute Giardiasis

Abstract: G. lamblia infection induces long-term, albeit variable, cellular immune responses that are not assemblage specific and that are largely driven by CD4 T-cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Increased levels of T cell markers specific for Giardia-exposed individuals have been shown before (22). Also in the present study, CD45RO/HLA-DR CD4 T cell responses were shown to be significantly elevated in SSA-and SSB-stimulated cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Increased levels of T cell markers specific for Giardia-exposed individuals have been shown before (22). Also in the present study, CD45RO/HLA-DR CD4 T cell responses were shown to be significantly elevated in SSA-and SSB-stimulated cells.…”
Section: Discussionsupporting
confidence: 82%
“…IFN-␥ was se-creted, and cells were found to be proliferating in response to trophozoites, suggesting that Giardia-specific proliferation of CD4 ϩ T cells exists in humans as well (21). CD4 ϩ T cell memory immune responses in peripheral blood mononuclear cells (PBMCs) from humans were investigated 5 years after a large outbreak of Giardia occurred (22). Giardia-specific CD4 ϩ T cell responses were found to be present by the upregulation of surface activation markers (CD25/CD26 and CD45RO/HLA-DR) and higher proliferation rates of T cells in Giardia-exposed persons compared to those in controls.…”
Section: Decreased or Nonexistent Cd4mentioning
confidence: 99%
“…The relative abundances of T cell populations within the IEL, however, are unaltered throughout infection in our model. The proliferation of Giardia-specific CD4 ϩ T cells has been reported in mice and humans (37)(38)(39). Several studies have shown that CD4 ϩ T cells are necessary for clearance of Giardia infections, and recent data have suggested that interleukin-17 (IL-17) is a key cytokine in mediating this protective effect (reviewed in reference 40).…”
Section: Infection With G Duodenalis Results In Increased Cd4mentioning
confidence: 99%
“…In severe cases of giardiasis, during infection Giardia trophozoites attach to the epithelium of the proximal small bowel aided by their ventral adhesive discs, evade host defenses possibly by undergoing genetic variation (12), and produce local alterations of villus structure and cellular apoptosis. The most devastating effects of Giardia infection are related to damage of the absorptive small bowel mucosa, together with abnormal intestinal immunity that favors chronic infection (13,14). While there is little evidence that preexistent malnutrition in young children makes them more susceptible to Giardia infection, once they are infected, persistent symptoms and health consequences are more likely to develop (15).…”
Section: Discussionmentioning
confidence: 99%